CODE MIXING IN FOURTH-SEMESTER STUDENTS AT UNDIKMA - Ni Wayan Prami Wahyudiantari (Journal of English Education and Literature, 2025)
This study explores the phenomenon of code mixing among fourth-semester university students, focusing on the linguistic patterns, motivations, and sociocultural factors that influence this practice in both academic and social contexts. Using a descriptive qualitative methodology, data were collected through classroom observations, recorded student interactions, and semi-structured interviews. Qualitative descriptive method is used in analyzing the data because it explained with words, phrases, and sentences. The data based on the words of the fourth semester students at UNDIKMA. In collecting data, the researcher used observational and non-participatory methods, and also taking notes. The analysis employs Muysken’s typology and Criper and Widdowson’s sociolinguistic framework to classify and interpret code mixing instances. Findings reveal that students frequently engage in intersentential and intrasentential code mixing, primarily between Indonesian and English, with occasional insertion of regional languages. Motivations include identity expression, communicative efficiency, social solidarity, and the influence of digital media. This study contributes to a deeper understanding of bilingual language use in higher education and offers implications for language teaching and policy.